2011
DOI: 10.1016/j.neuropsychologia.2010.09.029
|View full text |Cite
|
Sign up to set email alerts
|

The amygdala and decision-making

Abstract: Decision-making is a complex process that requires the orchestration of multiple neural systems. For example, decision-making is believed to involve areas of the brain involved in emotion (e.g., amygdala, ventromedial prefrontal cortex) and memory (e.g., hippocampus, dorsolateral prefrontal cortex). In this article, we will present findings related to the amygdala’s role in decision-making, and differentiate the contributions of the amygdala from those of other structurally and functionally connected neural re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(98 citation statements)
references
References 88 publications
(124 reference statements)
2
89
0
7
Order By: Relevance
“…Another recent review also concluded that, while the ability to implicitly learn associations between behaviors and valenced bodily reactions depends on the amygdala, the ability to automatically trigger these learned bodily reactions in later decision-making is dependent on VMPFC (Gupta et al, 2011). Thus, when deciding between multiple possible courses of action, the VMPFC appears necessary for generating the negative and positive bodily feeling states that bias our decisions based on past experience.…”
Section: Theories Of Emotionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another recent review also concluded that, while the ability to implicitly learn associations between behaviors and valenced bodily reactions depends on the amygdala, the ability to automatically trigger these learned bodily reactions in later decision-making is dependent on VMPFC (Gupta et al, 2011). Thus, when deciding between multiple possible courses of action, the VMPFC appears necessary for generating the negative and positive bodily feeling states that bias our decisions based on past experience.…”
Section: Theories Of Emotionmentioning
confidence: 99%
“…These loops would allow VMPFC to generate the valenced bodily feelings during deliberation (based on implicit statistical learning mechanisms) that guide decision-making, even in the absence of sufficient bodily feedback (Gupta et al, 2011). Figure 4A, the body perception hierarchy can also be considered an emotion perception hierarchy.…”
Section: An Integrative Multi-hierarchical Model Of Embodied Emotionmentioning
confidence: 99%
“…In some articles, obsessive-compulsive symptoms have even been proposed as a manifestation of an underlying decision-making deficit; seeking for an immediate relief of anxiety by compulsion (short-term reward) leads to functional impairment and compromises quality of life in the long term (negative long-term con-of dice task (GDT) (Brand et al, 2005a), respectively. The IGT requires the development of implicit preference for advantageous choice under ambiguous reinforcement contingencies (decision-making under ambiguity), which is mediated by emotional learning (Bechara et al, 2000a) and relevant structures, such as the orbitofrontal/ventromedial prefrontal cortex and amygdala (Bechara, 2004;Bechara et al, 1999Bechara et al, , 2000bGupta et al, 2011). In a previous study of individuals with ventromedial prefrontal lesions, poor IGT performance was also influenced by reversal learning (Fellows and Farah, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Fronto-temporal mechanisms are responsible for optimum regulation of emotional-based behavior (Gupta, Koscik, Bechara & Tranel, 2011), adequate frontal regulation to emotional-based responses represent an important prerequisite for interpersonal and social interactions, allowing subjects to regulate verbal and behavioral interactions; these processes are fundamental for socially-adjusted behavioral and personality development during childhood (Damasio, 2005). Based on genetics studies low serotonin metabolism has been outlined as the key neurotransmitter system for behavioral-impulsivity and aggression in ADHD (Oades et al, 2008).…”
Section: Impulsivity As a Fronto-temporal-adhd Typementioning
confidence: 99%